Effect of the Degree of canal Moisture on the Fracture Resistance of Endodontically Treated Teeth Roots Using Different Sealers (In Vitro Study) - Alomar, Alaa Abdulrahman; Alhalabiah, Hassan (Journal of medical and pharmaceutical sciences, 2024)
The aim of this invitro study is to evaluate the effect of the Degree of canal Walls Moisture and different root canal sealers (Bio ceramic (MTA fillapex), and Resin-based sealers (ADSEAL)) on the fracture resistance of endodontically treated teeth. Materials and Methods:40 extracted mandibular premolars were selected with completed, straight and single canal roots and free of caries or resorption or any previous treatment. The tooth crowns were removed and root length was adjusted to 16mm. Teeth were divided into four groups (n:10), Group1: drying with paper points and obturation with ADSEAL Group 2: drying with Alcohol70% and obturation with ADSEAL, Group 3 : drying with Alcohol70% and obturation with MTA fillapex , Group 4: drying with paper points and obturation with MTA fillapex .The root were vertically loaded with testing machine (Tinius Olesn H50KS) and the load when fracture was detected was recorded in newton. All statical analysis was performed at 95% level of confidence. Conclusion: Based on this in vitro study, Bioceramic-based sealer was more effective when compared with Resin-based sealers and drying 70% Alcohol with Resin-based sealers and drying paper points with Bioceramic-based sealer enhanced the fracture resistance of endodontically treated teeth.